2006
DOI: 10.1371/journal.ppat.0020085
|View full text |Cite|
|
Sign up to set email alerts
|

Alpha-Herpesvirus Infection Induces the Formation of Nuclear Actin Filaments

Abstract: Herpesviruses are large double-stranded DNA viruses that replicate in the nuclei of infected cells. Spatial control of viral replication and assembly in the host nucleus is achieved by the establishment of nuclear compartments that serve to concentrate viral and host factors. How these compartments are established and maintained remains poorly understood. Pseudorabies virus (PRV) is an alpha-herpesvirus often used to study herpesvirus invasion and spread in the nervous system. Here, we report that PRV and herp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 65 publications
5
101
1
Order By: Relevance
“…Feierbach et al found that actin filaments are formed in the nucleus of cells infected with PRV or HSV-1. Because these actin filaments associated with viral capsids during capsid assembly and were similar to the ones seen by SBFSEM [33], the authors concluded that intranuclear filaments are composed of actin. The function of nuclear actin during infection is currently unknown.…”
Section: Viral Replication and Capsid Assembly In The Nucleusmentioning
confidence: 59%
See 4 more Smart Citations
“…Feierbach et al found that actin filaments are formed in the nucleus of cells infected with PRV or HSV-1. Because these actin filaments associated with viral capsids during capsid assembly and were similar to the ones seen by SBFSEM [33], the authors concluded that intranuclear filaments are composed of actin. The function of nuclear actin during infection is currently unknown.…”
Section: Viral Replication and Capsid Assembly In The Nucleusmentioning
confidence: 59%
“…The actin cytoskeleton and associated proteins are also implicated in herpesvirus capsid assembly and nuclear egress [32,33,41]. Capsid assembly and genome packaging occurs in the nucleus in higher order structures that might depend on F-actin for their formation [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations